Ali na izsledkih temelječa medicina s kliničnimi smernicami zdravnika omejuje? - Drinovec, Jože (Zdravniški vestnik, 2006)
Background Evidence-based medicine with clinical practice guidelines represents a concept of clinical decisioning based on the current evidence. Clinical practice guidelines are systematically developed points of view meantto help both a physician and a patient in making decisions about the careof the individual patient. Clinical practice guidelines represent only a basic guidance to be considered by a physician in a specific clinical case andthat can be upgraded by considering the patient's comorbidity and other circumstances.. It is estimated that clinicalguidelines are followed by 70% ofEuropean physicians. Conclusions Clinical practice guidelines are not just simple recipes for patient treatment and also not a means of economizing in the health services and cannot be used in legal actions. For ethical decision making in medicine it is crucial to use the latest scientific achievements. Correctly understood and used clinical practice guidelines do not represent anobstacle for the patient's independency and creativity.
Keywords: Ethics, Medical; Etika medicinska; Evidence-Based Medicine; medicina; medicine; odločanje; Poklicna avtonomija; Practice Guidelines; Praktična navodila; pravice; Professional Autonomy; raziskave; zdravniki; zdravniška etika; Znanstveno utemeljena medicina